Exercise‐induced increase in M2 macrophages accelerates wound healing in young mice. Issue 19 (5th October 2022) - Kawanishi, Makoto; Kami, Katsuya; Nishimura, Yukihide; Minami, Kohei; Senba, Emiko; Umemoto, Yasunori; Kinoshita, Tokio; Tajima, Fumihiro
Abstract: Moderate‐intensity exercise performed during wound healing has been reported to decrease inflammatory cytokines and chemokines and accelerate wound healing. However, its effect on macrophage phenotype and the mechanism by which exercise accelerates wound healing remain unclear. The purpose of this study was to investigate the effect of exercise on macrophage phenotype during wound healing and to clarify the relationship between angiogenesis and wound healing. 12‐week‐old male C57BL/6J mice were divided into sedentary ( n = 6) and exercise groups ( n = 6). The exercise group performed moderate‐intensity treadmill running exercise (9.0 m/min, 60 min) for 10 days. Double immunofluorescence analysis was performed using F4/80 + inducible nitric oxide synthase (iNOS) + for M1 macrophages, F4/80 + transforming growth factor‐beta (TGF‐β)1 + for M2 macrophages, and CD31 + alpha smooth muscle actin (α‐SMA) + for angiogenesis. The exercise group showed significantly accelerated wound healing compared with the sedentary group. From early wound healing onward, exercise significantly inhibited M1 macrophage infiltration and increased M2 macrophage count. Exercise also significantly increased angiogenesis. Furthermore, the M2 macrophage phenotype was significantly correlated with angiogenesis in the exercise group, indicating that M2 macrophages and angiogenesis are related to accelerated wound healing. These findings suggest that moderate‐intensity exercise increases TGF‐β1 derived from M2 macrophages, which may be associated with enhanced angiogenesis and wound healing in young mice. Abstract : Moderate‐intensity exercise suppressed M1 macrophage‐derived iNOS and increased M2 macrophage‐derived TGF‐β1 in young mice. In addition, the increase in M2 macrophages may be associated with wound healing and angiogenesis.